The effects of cannabinoid 1 receptor compounds on memory: a meta-analysis and systematic review across species - Borgan, Faith; Beck, Katherine; Butler, Emma; McCutcheon, Robert; Veronese, Mattia; Vernon, Anthony; Howes, Oliver D. (Psychopharmacology, 2019)
Rationale While cannabis-based medicinal products have been shown to be effective for numerous neurological and psychiatric disorders, the evidence base regarding their adverse cognitive effects is poorly understood. The cannabinoid 1 receptor modulates memory performance via intracellular and extracellular mechanisms that alter synaptic transmission and plasticity. While previous literature has consistently shown that chronic cannabis users exhibit marked cognitive impairments, mixed findings have been reported in the context of placebo-controlled experimental trials. It is therefore unclear whether these compounds inherently alter cognitive processes or whether individuals who are genetically predisposed to use cannabis may have underlying cognitive deficits. Objective We conducted a meta-analysis to investigate the effects of full and partial cannabinoid 1 receptor (CB1R) agonists, antagonists, and negative allosteric modulators on non-spatial and spatial memory. Methods In accordance with the PRISMA guidelines, the EMBASE, MEDLINE, and PsycINFO databases were systematically searched for studies examining the effects of CB1R agonists, antagonists, and negative allosteric modulators on memory performance. Results We systematically reviewed 195 studies investigating the effects of cannabinoid compounds on memory. In humans ( N = 35 studies, comprising N = 782 subjects), delta-9-tetrahydrocannabinol (THC) (1.5–5 mg/kg) relative to placebo impaired performance on non-spatial memory tests, whereas only high THC doses (67 mg/kg) impaired spatial memory. Similarly, THC (0.2–4 mg/kg) significantly impaired visuospatial memory in monkeys and non-human primates ( N = 8 studies, comprising N = 71 subjects). However, acute THC (0.002–10 mg/kg) had no effect on non-spatial ( N = 6 studies, comprising 117 subjects; g = 1.72, 95% confidence interval (CI) − 0.18 to 3.63, p = 0.08) or spatial memory (9 studies, comprising 206 subjects; g = 0.75, 95% confidence interval (CI) − 1.09 to 2.58, p = 0.43). However, acute, full CB1R agonists significantly impaired non-spatial memory ( N = 23 studies, 519 subjects; g = − 1.39, 95% CI − 2.72 to − 0.06, p = 0.03). By contrast, the chronic administration of CB1R agonists had no effect on non-spatial memory ( N = 5 studies, comprising 146 subjects; g = − 0.05, 95% confidence interval (CI) − 1.32 to 1.22, p = 0.94). Moreover, the acute administration of CB1R antagonists had no effect on non-spatial memory in rodents ( N = 9 studies, N = 149 subjects; g = 0.40, 95% CI − 0.11 to 0.92, p = 0.12). Conclusions The acute administration of THC, partial CB1R agonist, significantly impaired non-spatial memory in humans, monkeys, and non-human primates but not rodents. However, full CB1R agonists significantly impaired non-spatial memory in a dose-dependent manner but CB1R antagonists had no effect on non-spatial memory in rodents. Moreover, chronic THC administration did not significantly impair spatial or non-spatial memory in rodents, and there is inconclusive evidence on this in humans. Our findings highlight species differences in the effects of cannabinoid compounds on memory.